2016
DOI: 10.1007/s00168-016-0772-7
|View full text |Cite
|
Sign up to set email alerts
|

Moving up and down the urban hierarchy: age-articulated interregional migration flows in the Netherlands

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Young people typically migrate to urban destinations, while counter-urban migration streams often have an overrepresentation of older adults (Plane & Jurjevich, 2009). This mobility pattern has not only been found in the US but also in various studies in Europe (see: De Jong et al, 2016;Friedrich &Warnes, 2000;Lindgren, 2003;Lundholm, 2012;Stockdale, 2006;Vollet et al, 2005).…”
Section: Introductionmentioning
confidence: 80%
“…Young people typically migrate to urban destinations, while counter-urban migration streams often have an overrepresentation of older adults (Plane & Jurjevich, 2009). This mobility pattern has not only been found in the US but also in various studies in Europe (see: De Jong et al, 2016;Friedrich &Warnes, 2000;Lindgren, 2003;Lundholm, 2012;Stockdale, 2006;Vollet et al, 2005).…”
Section: Introductionmentioning
confidence: 80%
“…At the later stages of urban development, alongside stronger economic diversifi cation and the growing popularity of alternative places of residence (Berry 1980), and due to the greater variety of consumer preferences (Long/Deare 1988), migration fl ows start taking other directions. People move from cities to suburbs and to rural areas, as well as between cities of different size and type (Champion et al 2014); not only up but also down the escalator (Fielding 1989(Fielding , 1992, and up and down the urban hierarchy (de Jong et al 2016). Migration trends in more densely populated territories differ from those in less populated areas (Stillwell et al 1990;Rees et al 1996).…”
Section: Previous Researchmentioning
confidence: 99%
“…The age groups are heterogeneous in terms of the reasons for and the objectives of migration: there is no common dominating motivation driving the migration of the middle-aged and the elderly. For example, de Jong et al (2016) fi nd that in the Netherlands, migrants aged 18-44 move between different levels of urban hierarchy in both directions: upwards when migrating to large cities, and downwards when going to smaller cities, and 70 percent of migrants aged 35-44 choose smaller cities as migration destinations. In France, the 23-33 age-group is the key contributor to suburbanisation, while in general, migration to the suburbs and rural areas increases with age (Détang-Dessendre et al 2008).…”
Section: Previous Researchmentioning
confidence: 99%
“…Mobility peaks between twenty and thirty and declines steadily afterwards, with an eventual rise around retirement age and again shortly before death. Many authors consider this strong empirical regularity as almost universal, which is shown by the wide use of Tom Wilson's "age schedule of migration" [5].…”
Section: Migration Age Profile Model (Map)mentioning
confidence: 99%